2017
DOI: 10.1021/acsnano.7b06294
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Modeling of Ion Migration Induced Degradation in Perovskite Solar Cells

Abstract: -With excellent efficiencies being reported from multiple labs across the world, device stability and the degradation mechanisms have emerged as the key aspects that could determine the future prospects of perovskite solar cells. However, the related experimental efforts remain scattered due to the lack of any unifying theoretical framework. In this context, here we provide a comprehensive analysis of ion migration effects in perovskite solar cells. Specifically, we show, for the first time, that (a) the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 39 publications
0
58
0
Order By: Relevance
“…Furthermore, ion migration under external electric field is considered as causing the accumulation of mobile ions at the interfaces [34]. Therefore, ion migration plays an important role in device hysteresis behavior [35][36][37]. In MAPbI 3…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ion migration under external electric field is considered as causing the accumulation of mobile ions at the interfaces [34]. Therefore, ion migration plays an important role in device hysteresis behavior [35][36][37]. In MAPbI 3…”
Section: Resultsmentioning
confidence: 99%
“…Representative errorbars are given in Figure 3 respectively. The faster degradation speed of MAPbI2Br1 was likely caused by ion migration 25 in MAPbI2Br1 as there is a more severe lattice mismatch with increasing bromine concentration [11][12]26 . The PL results in Figure S2 also confirmed this: the peak shift of MAPbI2Br1 is more significant than that of MAPbI2.5Br0.5 spectra.…”
Section: Stability Of Encapsulated Films Under Longer-term Illuminationmentioning
confidence: 99%
“…first revealed that perovskite is an ionic–electronic conductor, [ 9 ] many theoretical modeling and experimental results indicate that the intrinsic ions of perovskite (e.g., MA + , Pb + , I − ) have lower activation energies which result in the diffusion of these ions under low external bias or illumination conditions, leading to the rapid degradation of perovskites. [ 10–12 ] Meanwhile, the electromigration of I − ion corrodes the electrodes which severely influence the device performance. [ 13 ] Moreover, in regular structure of PSCs, the most widely used hole transport layer, 2,2′,7,7′‐tetrakis( N , N ‐di‐ p ‐methoxyphenylamine)‐9,9′‐spirobifluorene (Spiro‐OMeTAD) usually requires dopants, for example, lithium bis(trifluoromethyl sulfonyl)imide (LiTFSI) to enhance the conductivity.…”
Section: Introductionmentioning
confidence: 99%